THE DEVELOPMENT OF STUDENT WORKSHEET INQUIRY ORIENTED TO PRACTICE SCIENCTIFIC LITERACY ON FACTORS THAT AFFECTING REACTION RATES SUBMATTER (UNESA Journal of Chemical Education, 2019)
This study aims to develop student worksheets to practice scientific literacy based on feasibility in terms of content validity, construct validity, practicality, and effectiveness. The type of this reasearch refers to the method of Research and Development (R&D) adaptation of Sugiyono (2015) which was confined only to preliminary field testing stage. The instrument that is used were review sheets, content and construct validation sheets, learning outcomes test (pretest and posttest), student activities sheets and student responses sheets. This worksheets was tested on 12 students of 11th grade in SMAN 1 Krian. The result showed the worksheets that developed was valid viewed from content validity that obtained a percentage in range between 82.23%-89.99% with highly valid category, and viewed from construct validity 84.45%-93.33% with highly valid category. Practicality viewed from the result of student responses that obtained a percentage in range between 87.50%-94.45% with highly practical category which supported by observational student activities that obtained a percentage in range between 95.56%-99.51% with highly practical category. Effectiveness viewed from increasing student scientific literacy score through increasing n-gain that obtained scores in the range between 0.65-0.82 with range of categories between medium to high which is supported by the results of students completeness that obtained a percentage of 100% with complete category. Keywords: Worksheets, Scientific Literacy, Inquiry, Factors that Affecting Reaction Rates